Inflammatory Abdomen - de Oliveira Lima Ferraz, Pedro; Benatti, Lucas; Nasr, Adonis; Lopes Matins Filho, Eduardo; Llanos, Juan Carlos [UNESP]; Lopes Matins, Eduardo; Abreu, Phillipe (Springer Nature, 2025)
Acute abdomen refers to a clinical syndrome in which the patient has an acute onset of abdominal pain that requires immediate treatment, often surgical, sometimes even when the etiology of the syndrome is still unknown. Any abdominal or retroperitoneal organ may be responsible for this clinical entity, and the causes are classified into five different groups according to the etiopathogenesis as inflammatory, perforating, obstructive, vascular, and hemorrhagic. When not diagnosed and treated early, the patient may evolve rapidly with worsening of symptoms and progressive deterioration of systemic signs, reflecting the severity of this syndrome and the need for a fast diagnosis and treatment.